Transforming Prescription Opioid Practices in Primary Care With Change Theory. (December 2021) - Carpenter, Rob E.; Silberman, Dave; Takemoto, Jody K
The opioid epidemic continues to be an ongoing public health crisis. Many primary health care providers aptly serve as the gatekeeper to opioid prescriptions. The opioid epidemic has challenged the primary care profession whilst many of these providers have opted out of opioid prescribing altogether. This unintended consequence affirms erosion to primary care that is vital to the ecosystem of opioid management. The purpose of this study was to understand strategies to deliver opioids safely and effectively. Results indicate primary care providers are uniquely positioned to make a positive opioid impact through focused change initiatives. Five common themes arose from the inductive analysis: (1) provide leadership support; (2) define standard of work; (3) conduct pre-visit reviews; (4) conduct post-visit reviews; and (5) measure progress. Then, each common theme was deductively analyzed through a view of Kotter's change theory to support an effective proxy for implementing and sustaining chronic opioid therapy in a primary care context. These finding have potential to provide actionable implications for health care management professionals and primary care organizations such as hospitals and group practices.